Cognitive and Brain Gray Matter Changes in Children with Obstructive Sleep Apnea: A Voxel-Based Morphological Study - Hongbin, Li; Zhuo, Li; Guixiang, Wang; Jing, Zhao; Hua, Wang; Yue, Liu; Binbin, Nie; Jie, Zhang; Jun, Tai; Xin, Ni (Neuropediatrics, 2023)
Background To explore the neural difference between children with obstructive sleep apnea (OSA) and healthy controls, together with the relation between this difference and clinical severity indicator of children with OSA.Methods Twenty-seven children with OSA (7.6 ± 2.5 years, apnea hypopnea index [AHI]: 9.7 ± 5.3 events/h) and 30 healthy controls (7.8 ± 2.6 years, AHI: 1.7 ± 1.2 events/h) were recruited and matched with age, gender, and handedness. All children underwent 3.0 T magnetic resonance imaging of the brain and cognitive testing evaluating. Volumetric segmentation of cortical and subcortical structures and voxel-based morphometry were performed. Pearson's correlation analysis was performed between these features of gray matter volume (GMV) and obstructive apnea index (OAI) among children with OSA.Results In the comparison of children's Wechsler test scores of full-scale intelligence quotient and verbal intelligence quotient, the OSA group was significantly lower than the control group (p < 0.05). Compared with the control group, the GMV of many brain regions in the OSA group was significantly decreased (p < 0.05). In the correlation analysis of GMV and OAI in OSA group, right inferior frontal gyrus volume was significantly negatively correlated with OAI (r = − 0.49, p = 0.02).Conclusion Children with OSA presented abnormal neural activities in some brain regions and impaired cognitive functions. This finding suggests an association between the OSA and decreased GMV in children.
Keywords: children; obstructive sleep apnea; voxel-based morphometry; magnetic resonance imaging; gray matter volume